The effect of utilising magic box to improve students’ motivation in learning English: Deep learning practices - Lina Dwi Lestari; Waris Waris; Fauzan Adhim (Universitas Muhammadiyah Malang, 2025)
These days, the government has dealt with the new curriculum, called deep learning approach. Still, during the implementation deep learning approach in teaching-learning English at Vocational school, it showed that most students struggle with learning enthusiasm and motivation. Further, this research aimed at investigating the use of Magic Box to improve students’ learning motivation in learning English at SMK Negeri 1 Tempeh during deep learning. This research used explanatory mixed methods. A purposive sampling was used to select the sample. In addition, the research sampling was class X TKJ 1 consisting of 27 students was used as the control class, and class X TKJ 2 consisting of 25 students was used as the experimental class. In collecting the data, the researcher used observation and questionnaire, and semi-structured interviews. The results showed that the use of Magic Box media in deep learning was able to significantly increase students' learning motivation. This can be seen from the students’ enthusiasm and engagement during the learning process, where students became more interested, engaged and involved in classroom learning activity. In short, using Magic Box in teaching-learning English during deep learning process, is expected to promote students’ involvement and engagement, and increase self-confidence and learning outcomes.